Analisis SWOT Pengembangan Usaha Tempe di Desa Tambakberas - Tiara Ayu Nugraha Putri; Ika Puspitasari Dyah Rahmadhani; Purbowo Purbowo (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
The production of tempe is the most prevalent small and medium-sized enterprises (SMEs) in Indonesia. The popularity of tempe among Indonesians is closely linked to its health benefits. The high consumption rate of tempe indicates significant potential for the industry, particularly for SMEs involved in its production. A home-based tempe business in Tambak Beras Village, Jombang Regency, exemplifies such an SME. Despite its considerable potential, observations reveal that the business faces several challenges, including the absence of a governing institution or agency, poor financial management, and a labor shortage. This study uses SWOT analysis to formulate an appropriate development strategy for tempe production in Tambakberas Village, Jombang Regency. The research employs descriptive and quantitative methods to analyze development strategies for tempe SMEs. The data was collected in 2024 in Jombang Regency. The purposive sampling was used to select the study sample. Data was collected by observation and interviews. Then, the data was analyzed using SWOT analysis and the EFAS and IFAS matrix. The results showed that the tempe in Tambakberas Village, Jombang Regency, holds a strong internal position with an internal key factor score of 1.10. The EFAS matrix analysis reveals an external key factor score of 1.55, indicating that the business is well-positioned to capitalize on opportunities while managing industry threats. Based on the IE matrix derived from the EFAS and IFAS matrices, the tempe business in Tambakberas Village is located in Quadrant I. This positioning suggests that an aggressive strategy is recommended to foster growth, given that the Tempe business has internal strengths that align with external opportunities. The research implies that the home industry needs to improve Human Resources competency, optimize financial management, and expand the tempe business.